Glycoxidative profile of cancer patient serum: A clinical result to associate glycation to cancer. (29th November 2019) - Khan, Hamda; Alouffi, Sultan; Alatar, Abdulrahman A; Qahtan, Ahmad A; Faisal, Mohammad; Ahmad, Saheem
Abstract: The influence of advanced glycation end products (AGEs) in the biological processes contribute to the life-changing complications such as progression of cancer, diabetes and other chronic disorders. The receptor of AGEs while interacting with its ligands causes a never-ending irregularity in the cell-signaling communication. Hence, AGEs are considered as an important link between progression and contribution to cancer. This study focuses on the presence and/or absence of oxidative and glycative stress in the serum samples of various cancer patients. During analysis of the early and intermediate glycation product in cancer patient's sera, our result indicates an increasing trend of both the adducts as compared to normal healthy subjects. Similarly, one of the AGEs i.e., carboxymethyllysine was found to be enhanced in cancer sera as compared to NHS. The binding characteristics of circulating auto-antibodies in cancer patient's sera against human serum albumin (HSA)-AGEs were assessed through ELISA and furthermore, the maximum percent inhibition against HSA-AGEs was observed as 57–63%, 46–62% and 42–64% in prostate cancer, lung cancer and head and neck cancer. Hence, our result successfully assisted the presence of AGEs in all the cancer patient's sera though it is not clear which specific cancer is more potent to AGEs.